Faktor-Faktor yang Mempengaruhi Pengetahuan Ibu Hamil tentang Asfiksia Neonatorum - Riana, Hernah; Afni, Nur; Jumiyati, Jumiyati (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2024)
Neonatal asphyxia is one of the causes of lack of blood flow or gas exchange to or from the fetus in the period immediately before, during, or after the birth process. According to data from the World Health Organization (WHO), 28 billion babies die after the first 28 days because that time is the adaptation period experienced by babies to determine whether they can survive or not. One of the leading causes is asphyxia, which results in 11% of infant deaths. This research aims to determine the factors that influence pregnant women's knowledge about neonatal asphyxia based on age, parity, and maternal education. This research is an analytical survey with a cross-sectional approach in the Kolakaasi Community Health Center work area. The research sample used was 75 respondents with a questionnaire instrument. The research results show that the statistical test results using the chi-square test, the probability is smaller α (p < α) (0.001 <0.05). This result statistically shows that there is a significant relationship between age, parity, and maternal education on knowledge about neonatal asphyxia. Therefore, it can be concluded that age, parity, and maternal education influence maternal knowledge regarding neonatal asphyxia.